Organized Criminal Terrorism : An International Law and International Relations Perspective - Akestoridi, Katerina,; Rocha, Inmaculada Marrero,; Seatzu, Francesco, (International Law E-Books Online, Collection 2025., 2024)
In this book contributors engage into the theoretical dialogue about the interplay between terrorism and organized crime. Arguing in favor of its existence, the authors of the book seek to define the phenomenon of 'organized criminal terrorism'